CuAAC-based assembly and characterization of a ruthenium–copper dyad containing a diimine–dioxime ligand framework. (9th March 2017) - Queyriaux, Nicolas; Andreiadis, Eugen S.; Torelli, Stéphane; Pecaut, Jacques; Veldkamp, Brad S.; Margulies, Eric A.; Wasielewski, Michael R.; Chavarot-Kerlidou, Murielle; Artero, Vincent
Abstract : The design of molecular dyads combining a light-harvesting unit with an electroactive centre is highly demanded in the field of artificial photosynthesis. The versatile Copper-catalyzed Azide–Alkyne Cycloaddition (CuAAC) procedure was employed to assemble a ruthenium tris-diimine unit to an unprecedented azide-substituted copper diimine–dioxime moiety. The resulting Ru II Cu II dyad4 was characterized by electrochemistry, 1 H NMR, EPR, UV-visible absorption, steady-state fluorescence and transient absorption spectroscopies. Photoinduced electron transfer from the ruthenium to the copper centre upon light-activation in the presence of a sacrificial electron donor was established thanks to EPR-monitored photolysis experiments, opening interesting perspectives for photocatalytic applications.